Permainan Edukasi "Oper ke Dinding": Solusi Kreatif untuk Pembelajaran Operan Dada dalam Bola Basket - Lalu Moh Yudha Isnaini; Ari Wibowo Kurniawan; Gosy Endra Vigriawan; Andry Akhiruyanto; Mohad Anizu Mohd Nor (Indonesian Journal of Physical Education and Sport Science, 2026)
Study Purpose : One of the barriers to teaching basic chest pass learning in basketball is the monotonous approach that reduces students' motivation and engagement. The purpose of this study was to create and assess a projector-based educational game, Pass To The Wall that used an innovative medium for learning the chest pass. Material and Methods. This study used the ADDIE model of Research and Development (R&D) design. A small trial involved thirty-two junior high school eighth graders. Data were collected from accomplished observations, student and teacher response questionnaires and followed by a quasi-experimental the pre-test and post-test of chest pass skills. Results. Pass To The Wall projector-based educational game was highly feasible and effective in its development and implementation. Media received very positive responses from students (87.5%) and teachers (91.3%). Moreover, statistical analysis showed significant differences in chest pass after intervention; importantly the difference was not just in number but also technique (p < 0.05). The results indicate that the projector based educational game produced a statistically significant improvement in students basketball chest pass performance. Conclusion. In conclusion, the findings of this study showed that Pass To The Wall educational game is actionable and effectively use as instructional medium to enhance students basketball chest pass skills. With the integration of projector-based interactive media, not only is technical accuracy and execution improved, but it also enhances student engagement of physical education learning. Thus, the current model can be considered as an alternative strategy for the development of fundamental motor skills in basketball teaching.